2020
DOI: 10.5812/ijcm.98325
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ER, PR, Ki67 and HER-2/neu Reactivity Pattern with Patients’ Age, Histologic Grade, Tumor Size and Lymph Node Status in Invasive Ductal Breast Cancer

Abstract: Background: Breast cancer is the most prevalent neoplasm diagnosed in Iranian women. Objectives: The current study was performed to measure the hormone receptor status and its possible connection with the patient’s age, tumor size, histological grade, and lymph node status and involvement in patients with invasive ductal breast cancer (IDBC) Methods: A total of 103 women with IDBC recently diagnosed at the Department of Pathology of Shohada-E-Tajrish Hospital were entered into this study. The mean age of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Lymph node involvement was seen in 56.4% of the cases in our study, which corresponds to studies by Ambroise et al [16] (58.19%) and Aly et al [17] (61.8%). Ahadi et al study [18] showed lymphovascular and perineural invasion in 54.2% and 16.5% cases, which were similar to our study (65.5% and 16.4% respectively). Histological grading (Modified Blood Richardson score) was done in all the cases and grade II was found to be the most common (54.5% cases), which was like that noted in studies done by S. Siddiqui Aziz study [19] (2003) and Vanisha Dhaka et al [20] Sulhyan K R et al [21].…”
Section: Discussionsupporting
confidence: 91%
“…Lymph node involvement was seen in 56.4% of the cases in our study, which corresponds to studies by Ambroise et al [16] (58.19%) and Aly et al [17] (61.8%). Ahadi et al study [18] showed lymphovascular and perineural invasion in 54.2% and 16.5% cases, which were similar to our study (65.5% and 16.4% respectively). Histological grading (Modified Blood Richardson score) was done in all the cases and grade II was found to be the most common (54.5% cases), which was like that noted in studies done by S. Siddiqui Aziz study [19] (2003) and Vanisha Dhaka et al [20] Sulhyan K R et al [21].…”
Section: Discussionsupporting
confidence: 91%